A potential means to help the HPV vaccine penetrate the Japanese public while under the continued suspension of governmental recommendation - Natsuyo Ugumori; Yutaka Ueda; Asami Yagi; Hazuki Abe; Mayu Shiomi; Satoshi Nakagawa; Kosuke Hiramatsu; Ai Miyoshi; Eiji Kobayashi; Toshihiro Kimura; Tadashi Kimura; Motowo Nabeta (Taylor & Francis Group, 2021)
In Japan, the government's recommendation for the HPV vaccine has been suspended for almost 8 years. A questionnaire survey was conducted in the Tsubaki Women's Clinic, Matsuyama, Japan, to examine responses of the mothers of girls eligible for HPV vaccine before and after their doctor provided them an informative leaflet explaining the need for cervical cancer prevention. Among the 53 mothers who admitted to imposing some preconditions before being willing to encourage their daughters' HPV vaccination, 21 (40%) mothers became more willing to vaccinate their daughters immediately after receiving the cervical cancer prevention linkage explanation provided by their doctor, and seven of the mothers (33%) even returned to the clinic to get their daughter vaccinated during our study period. Logistical regression analysis revealed that having initial preconditions required for their daughters' HPV vaccination was an independent variable influencing the mothers' change of willingness to get their daughters vaccinated immediately after receiving the explanation using the leaflet. We have found that to achieve maximum effectiveness, we can use an appropriate leaflet even under suspension of the governmental recommendation. Our future efforts should be focused on those mothers who are less likely to impose preconditions on their daughter's vaccination.